Lovebirds - Ismail, Mohd Firdaus; Abdul Aziz, Nor Akmar; Mohamed Mokhtar, Mohamed Daniel (Universiti Putra Malaysia Press, 2015)
The romance of birds are expressed and manifested in how they impress and attract their love counterparts. The colourful males such as the peacock (Pavo cristatus) and the golden pheasant (Chrysolophus pictus) would undergo detailed grooming to ensure flawless appearance to impress the beloved in the competitive world of the wild. The males of certain species would pour their dedication and effort to build the mating court as splendid as a castle to invite the queen of their heart such as shown by the bowerbird (Ptilonorhynchus violaceus) and the baya weaver (Ploceus philippinus).